2023
DOI: 10.1039/d2tb01338j
|View full text |Cite
|
Sign up to set email alerts
|

Zn doped iron oxide nanoparticles with high magnetization and photothermal efficiency for cancer treatment

Abstract: Magnetic nanoparticles (NPs) are powerful agents to induce hyperthermia in tumours upon the application of an alternating magnetic field or an infrared laser. Dopants have been investigated to alter different...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…1 B, with increased power and time in microwave-assisted synthesis, a peak shift towards larger angles appeared in nanocatalysts, which increased the distance between the plates (311) and the lattice constant. During the synthesis by microwave-assisted, with the growth in power and radiation time, the temperature rises, which induces doping NH 4 Cl in the Fe 3 O 4 's nanocatalysts 33 . It is primarily due to the extensive ionic radius of NH 4 + (143 pm) compared to Fe +3 (64.5 pm) which is predicted to extend the crystal 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 B, with increased power and time in microwave-assisted synthesis, a peak shift towards larger angles appeared in nanocatalysts, which increased the distance between the plates (311) and the lattice constant. During the synthesis by microwave-assisted, with the growth in power and radiation time, the temperature rises, which induces doping NH 4 Cl in the Fe 3 O 4 's nanocatalysts 33 . It is primarily due to the extensive ionic radius of NH 4 + (143 pm) compared to Fe +3 (64.5 pm) which is predicted to extend the crystal 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that all samples have been washed frequently using sufficient deionized water to conclude that NH 4 Cl is not eliminated by washing, and it dops on the Fe 3 O 4 nanocatalysts. The prominent peaks' intensity and displacement would be examined to investigate and prove this issue 33 , 34 The most substantial diffraction peak from the plane (311) to investigate the peak shift by altering the purity of the samples was determined to examine the structural changes of the crystal unit. Figure 3 shows the magnification of the diffraction intensity from the plane (311).…”
Section: Resultsmentioning
confidence: 99%
“…Doped-IONPs can be synthesized by coprecipitation (CP), green combustion (GC), sol–gel process (SGP), chemical polymerization approach (CPA), microwave-assisted process (MAP), hydrothermal approach (HDA). ,,,,, Multiple types of dopants, e.g. , cobalt, nickel, copper, zinc, and rare-earth elements are broadly applied for doping purposes. ,,,, At present, doped-IONPs have found widespread applications in drug delivery, antimicrobial and anticancer activities, MRI imaging agent. Moreover, when doped-IONPs are employed as antimicrobial agents, transition metals are mainly utilized due to their antimicrobial characteristics in their bulk form …”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
“…For this reason, mixed ferrites doped with metal ions such as Co, Zn or Mn are explored. 99,100 In vivo studies demonstrated tumor inhibition at safe MHT conditions, once their toxicity limits have been accurately defined. 81,101 Other strategies have been investigated using heterostructures including iron-based elements such as metallic iron or wu ¨stite in core@shell configurations that proved effective for triggering cancer cell death via MHT.…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%